Spatial Prioritisation of Management for Biodiversity Conservation Across the Eu - Alvarez-Miranda, E (ELSEVIER SCI LTD, 2022)
The last report on the State of the Nature in the European Union (EU), a periodic monitoring exercise at continental scale, shows that biodiversity continues to decline, despite the efforts done in the last decades. Urgent action is, therefore, needed to reverse this trend. Effective conservation must rely on careful planning and strategic investment of limited resources to maximise efficiency of conservation efforts. Here, we carry out a gap analysis to identify pressures and threats with no reported management action over the period 2013-2018 and identify priorities to close this gap. We use information from the State of Nature report to identify combinations of species/habitats x pressures/threats affecting them with no management action reported. We finally prioritise the selection of pressures and threats to be addressed for all species and habitats collectively. We found that 2/3 of all combinations of species/habitat x pressure/threat did not have management actions reported. Management gaps were especially large for birds, amphibians and reptiles and marine bioregions in northern EU. This management gap affects 98 % of Natura 2000 sites, with at least one species/habitat with no management action reported for one or more pressures/threats. The spatial prioritisation analyses showed that all species and habitats could benefit collectively from a reduction in 30 % of pressures/threats incidence by targeting a small proportion of pressures/threats and Natura 2000 sites. The prioritisation approach that we demonstrate here could be valuable to plan investment to close the current management gap and inform conservation across the EU.